1995
DOI: 10.1083/jcb.131.2.275
|View full text |Cite
|
Sign up to set email alerts
|

ADAM, a novel family of membrane proteins containing A Disintegrin And Metalloprotease domain: multipotential functions in cell-cell and cell-matrix interactions.

Abstract: ELL--cell and cell-matrix adhesion, as well as proteolysis of the extracellular matrix, are vital for normal processes such as tissue morphogenesis and wound healing, as well as for pathologies such as tumor cell invasion and metastasis. A variety of cell surface adhesion proteins and proteases are important players in these events. Families of membrane-anchored cell surface adhesion molecules include cadherins, immunoglobulin superfamily members, selectins, integrins, and syndecans (7). Membrane-anchored cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
278
0
10

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 472 publications
(288 citation statements)
references
References 19 publications
0
278
0
10
Order By: Relevance
“…Fig. 2 shows the protein sequences of these bands are consistent with a known protein ADAM 10 [10], a metalloprotease with an ill-defined biological activity [11,12] (the lower band is a proteolyzed product starting at residue 285). ADAM 10 could cleave 125I-proTNFa to a 17 kDa protein (Fig.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Fig. 2 shows the protein sequences of these bands are consistent with a known protein ADAM 10 [10], a metalloprotease with an ill-defined biological activity [11,12] (the lower band is a proteolyzed product starting at residue 285). ADAM 10 could cleave 125I-proTNFa to a 17 kDa protein (Fig.…”
Section: Resultsmentioning
confidence: 61%
“…A homologous protein was recently purified from human Monomac 6 cells (data not shown). The protein was identified as ADAM 10 [10], a protein first purified from bovine brain based on its ability to cleave MBP [11,12]. The protein has since been found in many tissues, and is homologous to the Drosophila kuz protein, suggesting a role in neurogenesis [13].…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] ADAMs were initially discovered as proteins involved in fertilization, muscle fusion and organ development. 18,19 In this study, we provide evidence that proteins ADAM10, GTP-binding protein a13, radixin, myosin regulatory light chain and RhoA promote cell fusion in colon cancer cells. In addition, we demonstrate that cell fusion results in the acquisition of a resistant phenotype to both 5-FU and Oxa, two pharmacological agents commonly employed in the treatment of advanced colon cancer.…”
Section: Introductionmentioning
confidence: 67%
“…One of the best-characterized members of the ADAM family is TACE (ADAM-17), responsible for the ectodomain shedding of receptors for TNF and other cytokines (11,21). Using anti-TACE, which recognizes the extracellular, catalytic domain of TACE, we found that this enzyme is expressed in BAC macrophages and that its expression is inhibited by the pretreatment of cells with dec-RVKR-cmk (Fig.…”
Section: Resultsmentioning
confidence: 95%